Manajemen risiko pembiayaan sebagai kunci keberhasilan dan ketahanan jangka panjang perbankan syariah - Windiasari, Fica Afria (Maliki Interdisciplinary Journal, 2024)
In every organization and banking industry, risk management is undoubtedly present. Risk management in banks is an essential component in managing the success and long-term growth of financial institutions. This study aims to conduct an analysis of risk management implementation with the objective of identifying the risk management practices and their impact on company performance. The research methodology employed includes qualitative analysis based on literature review of risk management practices, as well as an assessment of their effectiveness in achieving bank objectives. The findings of this study show that the implementation of risk management in financing plays a very important role in ensuring the long-term success and resilience of a bank. Effective risk management practices can help banks manage risks related to financing, increase customer confidence, minimize losses, and achieve success.